Immanuel and Me With-Out Hyphen - Andre Gunder Frank (Journal of World-Systems Research, 2015)
This essay is my personal and intellectual tribute to Immanuel Wallerstein. It takes the form of my also personal intellectual account of our ?rst independent, then joint, and again increasingly separate journeys through the maze of the world [-] system with and without a hyphen. Imagine our relations as a horizontal Y shaped rope. It began with strands that, in the 1960s, ran parallel, becoming intertwined during the 1970s and 1980s until the strands (or at least some) separated again in the 1990s, going off in increasingly different directions like a horizontal Y. Why? My answer is both circumstantial and personal, in which the personal choices and trajectories are driven primarily by world and local political circumstance. Of course, my account re?ects my own perspective on this story. However it also includes other colleagues and friends of Immanuels and mine, in particular our co-authors in several books and edited volumes, Giovanni Arrighi and Samir Amin, with whom I can check this account. Others, alas, are no longer with us.